Evolution of goods and services tax in India - Kavita Rao R
Goods and Services Tax (GST) was implemented in India in July 2017, after four decades of protracted deliberations amid critical socio-economic and political challenges. GST is a comprehensive multistage value added tax (VAT) on goods and services where both central and state governments share the same tax base. Finding a suitable design for GST that encompasses taxes from both the centre and the state tax brackets makes the Indian GST unique among GST implemented in other federal countries. This book is a study of the evolution of GST in India since the Report of the Indirect Taxation Enquiry Committee of 1977. It studies the following issues on GST: a) inclusion and exclusion of taxes, b) finding a suitable mechanism to handle inter-state transactions, c) finding revenue neutrality of the tax reform, d) providing compensation to states for any possible loss of revenue due to its adoption, and e) possible scope for coordination in GST administration.--